Integrating carbon sequestration and yield optimization in Indian cropping systems - GV, Anupama; Das, Abhishek; Falk, Thomas; Melesse, Mequanint; Chander, Girish; Perumal, Cuba; Kumar, Abbhishek; Singh, Ajay; Mandapati, Roja (Elsevier, 2025)
Agriculture contributes significantly to greenhouse gas (GHG) emissions but also holds strong potential for mitigation – particularly through soil organic carbon (SOC) sequestration. This study evaluates the impact of integrated management practices—such as biochar application, optimized irrigation, and fertilizer management on yield improvement and SOC sequestration in semi-arid regions of Maharashtra, India. Using APSIM simulations across five districts and diverse cropping systems, it compares these practices with conventional farming. Results indicate that integrated practices consistently improve yields, SOC levels, and economic viability. For instance, maize yields under integrated practices increased by over 30 %, with substantial SOC gains. A cost-benefit analysis reveals high benefit-cost ratios, making these practices economically viable for smallholder farmers. This study highlights the transformative potential of integrated practices in addressing food security and environmental sustainability, especially in semi-arid regions. Policy recommendations include subsidizing biochar, promoting precision irrigation technologies, and integrating SOC sequestration strategies into national climate action plans. These findings provide actionable insights for scaling sustainable agricultural practices in resource-constrained settings. Previous article in